Case Report: Combined Intravenous Infusion and Local Injection of CAR-T Cells Induced Remission in a Relapsed Diffuse Large B-Cell Lymphoma Patient - Linhui Hu; Fan Wu; Huiping Wang; Weiwei Zhu; Juan Wang; Fengxiang Yu; Zhimin Zhai (Frontiers in Immunology, 2021)
Relapsed diffuse large B-cell lymphoma (DLBCL) is a disease with a poor prognosis. Recent clinical trials results showed chimeric antigen receptor (CAR) T cell therapy has a promising role in treating relapsed DLBCL. Unfortunately, patients with extranodal lesions respond poorly to CAR-T cells administered intravenously. Herein, we evaluated the efficacy and safety of a new treatment strategy of CAR-T cells, combining intravenous infusion with local injection of CAR-T cells, in a relapsed DLBCL patient with extranodal lesions. The patient achieved durable remission and without severe adverse effects after CAR-T cells treatment. During the follow-up period of one year, the patient remained in good condition. In conclusion, combining intravenous injection with a local injection for CAR-T cell is a feasible strategy for relapsed DLBCL patients with extranodal lesions.